2008
DOI: 10.1007/s10661-008-0394-3
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of sulphur and heavy metals in needles and rooting soils of Masson pine (Pinus massoniana L.) trees growing along an urban–rural gradient in Guangzhou, China

Abstract: Current (C) and previous year (C + 1) needles and soils (organic horizon, 0-10 cm and 10-20 cm mineral depth) of Masson pine (Pinus massoniana L.) trees were sampled at four forested sites (Huang Pu industrial district, HP; South China Botanical Garden, BG; Mao Feng Mt., MF; and Nan Kun Mt., NK) in Guangzhou along a urban-rural gradient and analyzed for sulfur (S) and heavy metals (Cu, Zn, Ni, Cd, Cr and Pb) concentrations. Needle concentrations of all the elements were significantly higher at industrial HP th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
3
25
2
1
Order By: Relevance
“…Having in mind the low mobility of Pb (low translocation to the aerial parts), and concerning the observed pattern of their content in leaf/needle and branch, it can be concluded that Pb arises from airborne emissions. Compared to the mean values reported in the literature (Yilmaz and Zengin, 2004;Al-Alawi and Mandiwana, 2007;Sun et al, 2009;Kord et al, 2010;Sun et al, 2010;Dmuchowski et al, 2011), concentrations of Pb in pine needles from our study area are higher. Similar or slightly lower Pb concentrations in linden leaves predominantly from traffic related sites were also reported by Piczak et al (2003), Tomašević et al (2004) and Aničić et al (2011).…”
Section: Leadcontrasting
confidence: 93%
See 3 more Smart Citations
“…Having in mind the low mobility of Pb (low translocation to the aerial parts), and concerning the observed pattern of their content in leaf/needle and branch, it can be concluded that Pb arises from airborne emissions. Compared to the mean values reported in the literature (Yilmaz and Zengin, 2004;Al-Alawi and Mandiwana, 2007;Sun et al, 2009;Kord et al, 2010;Sun et al, 2010;Dmuchowski et al, 2011), concentrations of Pb in pine needles from our study area are higher. Similar or slightly lower Pb concentrations in linden leaves predominantly from traffic related sites were also reported by Piczak et al (2003), Tomašević et al (2004) and Aničić et al (2011).…”
Section: Leadcontrasting
confidence: 93%
“…Pine needles have been determined to have higher Zn concentrations than the linden leaves, at the sampling sites where both plant species were sampled. Zn concentrations in pine needles have shown to be lower in our research than the concentrations in the studies of Yilmaz and Zengin (2004), Al-Alawi and Mandiwana (2007), Yang et al (2008), and Sun et al (2009). The content of Zn in linden leaves is similar to Zn concentrations in the research of Piczak et al (2003).…”
Section: Zincsupporting
confidence: 80%
See 2 more Smart Citations
“…2). The sampling methodology followed the orientations defined by Brooks (1983Brooks ( ), Ö zdemir (2005 and Sun et al (2009). The needles, stems and rooting soils of Pinus pinaster were collected at the five locations in late July and early August, during the dry season of the year.…”
Section: Sampling and Sample Preparationmentioning
confidence: 99%